EUGLENA MARINE BIOFUEL INNOVATING SUSTAINABLE LOW CARBON ENERGY FOR THE FUTURE OF SHIPPING - Miftakhul Naim (Jurnal Geosaintek, 2026)
The maritime sector accounts for nearly 3% of global greenhouse gas (GHG) emissions and is under increasing pressure to decarbonize. This paper presents a concept for an integrated port–ship biofuel supply chain utilizing Euglena gracilis  wax ester co-processed with waste cooking oil (WCO), drawing on advancements by Euglena Co., Ltd in Japan. The proposed pathway integrates large-scale hybrid  raceway fermenter cultivation, energy-efficient wet extraction using liquid dimethyl ether (DME), catalytic upgrading to drop-in green diesel/HEFA, and valorization of co-products. The inclusion of WCO expands lipid feedstock diversity, supports circular economy objectives, and lowers production costs. Literature-based techno-economic analysis (TEA) and life cycle assessment (LCA) indicate strong potential for producing renewable marine fuels that comply with international shipping fuel regulations. A phased R&D roadmap is outlined, featuring pilot trials on harbor tugboats integrated with renewable energy and CO₂ capture, aligning with Indonesia’s Asta Cita Point 5 on downstream industrialization and Point 2 on green economy and advancing SDG 7 and SDG 13 through a sustainable maritime biofuel value chain.